PRODUK KOSMETIK HALAL DENGAN PENDEKATAN PUSH PULL AND MOORING GUNA MENINGKATKAN SWITCHING INTENTION - Fitriani Fitriani; Yolanda Masnita Siagian (STMIK Widuri Jakarta, 2024)
Halal cosmetic products have become a major focus in the global beauty industry in response to increasing consumer demand for halal and safe products. This study analyzes effective marketing strategies using push, pull, and mooring approaches to increase consumer switching intentions to halal cosmetic products. The ‘push’ approach involves actively promoting products to consumers through social media, advertising, and campaigns that emphasize the benefits of halalness, quality, and safety. On the other hand, the ‘pull’ strategy focuses on creating product appeal through formulation innovation, attractive packaging, and consumer testimonials that strengthen trust in the halalness and superiority of the product. In addition, the ‘mooring’ approach associates halal cosmetic products with values that are relevant to consumers, such as environmental awareness, sustainability, and awareness of the product’s goodness for the skin. The results of the study show that the combination of push, pull, and mooring strategies simultaneously has a significant positive effect on consumer switching intentions to halal cosmetic products. This holistic marketing strategy strengthens consumers’ perceptions of halalness, quality, and added value of the product, triggering a desire to switch from conventional products to halal cosmetic products that are safer and in line with their values.